The impact of the "Green Transition" in the field of food packaging on the behavior of Romanian consumers - Alexandru Jurconi; Ioana Maria Popescu; Daniela-Ioana Manea; Mihaela Mihai; Rodica Pamfilie (Amfiteatru Economic Journal, 2022)
Sustainability has become one of the constant concerns of active participants in the food chain: producers, traders, consumers, and regulators. The paper aims to identify consumers' perceptions of the use of sustainable food packaging, in an exploratory survey of a sample of 280 respondents, knowing the importance of recycling to create a healthy and sustainable environment. The relevance of the research derives from the need to know the behavior of consumers in a certain geographical area, with regard to the aspects related to the recycling and sustainability of packaging. This is a component of green marketing that involves the management of activities related to the reconsideration of products and production processes, as well as the use of eco-sustainable packaging. The validation of the research hypotheses was done with methods of non-parametric analysis of the interdependencies between the identified variables, the results obtained highlighting the need to study this issue on a representative sample, using a more complex questionnaire. 81% of the study respondents identified as the main benefit for the use of sustainable packaging the possibility of living in a less polluted environment, an essential component of the development of ecological and sustainable food systems, being identified in the ability of producers and traders to communicate the placement on the market of sustainable packaging for marketed products.
Keywords: C25; D12; M31; M37; M38; O33; Q53; 330; consumer behavior; eco-innovation; eco-labeling; European Green Pact; green marketing; non-parametric analysis.; sustainable packaging